Cognitive-behavioral treatment of panic disorder with agoraphobia - Ponnusamy S.; Shazli Ezzat Ghazali (penerbit ukm, 2005)
This paper reports a clinical case study on the effectiveness of Cognitive- Behavioral Treatment (CBT) in treating panic attack with agoraphobia in a local health psychology clinic. M.N., a 24 year old male, complained of nightmares, heart palpitations, sweating, tremors and fearful feelings for thepast one and a half years. He felt anxious about going to crowded places such as bus stations, night markets, supermarkets, and mosques and being left alone in any place which he was not familiar with. This case study adopted an ABC design whereby the subject was assessed at three different phases: pre-treatment, mid-treatment and post-treatment. Four standard assessment measures were administered: Beck Anxiety Inventory (BAI), Beck Depression Inventory (BDI), Anxiety Scale of Minnesota Multiphasic Personality Inventory-2 (MMPI-2) and State-Trait Anxiety Inventory (STAI). The subject responded well to 12 sessions of intervention employed in the study based on CBT model and this could be noticed by minimal score on the entire psychological test administered. The application of behavioral and cognitive strategies became more effective due to patient’s ability to understand and also due to his cooperative behavior. He responded well to imagery exposure and in-vivo gradual exposure and successfully went to shopping malls, used lifts at Kuala Lumpur Tower, went to night markets and used public transport.